Persistence and Predictive Ability of Earnings: Evidence from France and the UK - Kimouche Bilal (Economics and Business)
The persistence and predictive ability are extensively requested as desirable attributes of earnings quality in the literature. The paper aims at investigating the persistence and predictive ability of earnings in French and UK companies. The study included a panel data of 1035 firm-year observations for 115 French listed companies from the CAC All-Tradable and 900 firm-year observations for 100 UK listed companies from the FTSE All-Share, during the period of 2011–2019. The research design was based on two equations starting from Sloan (1996) that were estimated using Fixed Effects Method. The study showed that earnings were persistent but they had no predictive ability regarding the future cash flows whether in French or UK companies and that earnings of UK companies were more persistent than those of the French companies. We argue that the persistence of earnings and the inability to predict future cash flows can be evidence of earnings management. The study contributes to the literature about earnings quality by studying earnings persistence and earnings predictive ability together in two different environments. The results require that users must take into consideration the illusory persistence of earnings, auditors must be cautious regarding the manipulation of earnings by managers, and accounting standard setters must review the reporting guidelines of cash flows to enhance their predictability by earnings.